(untitled) (Journal of Human Sciences, 2023)
The Arabic language occupies an important place in the Algerian educational methods, and it includes in the methods of the second generation of primary education four fields represented as the field of understanding the spoken and its related to the listening and understanding, the field of oral expression related to the viewing and oral expression, the field of understanding the written related to the reading and writing, and the field of written expression related to the production. In this research, we will focus on the first field; The field of understanding the operative, in an attempt to find out its role in understanding the other fields by enriching the student’s linguistic baggage, and helping him build his learning and acquiring targeted resources in each educational axis, and to determine the importance of listening in the learning process.